Upland rice growth and mineral nutrition as affected by cultivars and sulfur availability - Crusciol, Carlos Alexandre Costa [UNESP]; Nascente, Adriano Stephan; Soratto, Rogério Peres [UNESP]; Rosolem, Ciro Antonio [UNESP] (Wiley, 2013)
A better understanding of the differential growth of upland rice (Oryza sativa L.) cultivars with increasing soil S availability could help improve rice yield under upland conditions. The objective of this study was to evaluate root and shoot growth and nutrition of upland traditional and modern rice cultivars as affected by S availability. The experimental design was completely randomized in a 3 (rates of S) × 3 (cultivars) factorial with four replications. Low availability of S in the soil reduces root and shoot development and the efficiency of N, P, and S uptake, as well as the concentration and content of these nutrients in rice cultivars. At 0 mg dm-3 of S, rice cultivars prioritize root growth over shoots, and the traditional cultivar does so with greater intensity. Our results suggested that more development of traditional cultivars under low S availability facilitates its adaptation in soils under this condition. On the other hand, the intermediate and modern cultivars are more responsive to S fertilization. Moreover, S fertilization allows significant increases in upland rice growth and must be considered in cropping systems aiming for high yields. © Soil Science Society of America.
Keywords: Cropping systems; High yield; Mineral nutrition; Oryza sativa; Over-shoot; Rice cultivars; Rice yield; Root growth; S uptake; Shoot development; Shoot growth; Landforms; Nutrition; Soils; Sulfur; Plants (botany); crop yield; cropping practice; cultivar; experimental design; fertilizer application; growth rate; nutrient uptake; rice; soil nutrient; sulfur; upland region; yield response